Vous êtes sur la page 1sur 8

CALCULUS Limits.

Functions defined by a graph

1. Consider the following function defined by its graph:


e
y6
u
e 3

e 2

u 1
x
0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
−1

−2 e
u

−3 e

−4

Find the following limits:


a) lim − f (x) b) lim + f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−1 x→−1 x→−1 x→−4 x→4

2. Consider the following function defined by its graph:

y6
e 3 u
e

u
e 2

1 e
x
0 e
u -
−5 −4 −3 −2 −1 0 1 2 3 4 5
−1

−2

−3

−4

Find the following limits:


a) lim f (x) b) lim f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→1− x→1+ x→1 x→−5 x→5


c 2009 La Citadelle 1 of 9 www.la-citadelle.com
CALCULUS Limits. Functions defined by a graph
3. Consider the following function defined by its graph:

y6
e 3

u
e 2

1
x
0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
−1

u
e −2 e

−3 u

−4

Find the following limits:


a) lim f (x) b) lim f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−2− x→−2+ x→−2 x→−4 x→3

4. Consider the following function defined by its graph:

y6
3

2 e

1 u
x
e 0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
u −1 e
u

−2

−3

−4

Find the following limits:


a) lim− f (x) b) lim+ f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→2 x→2 x→2 x→−4 x→5


c 2009 La Citadelle 2 of 9 www.la-citadelle.com
CALCULUS Limits. Functions defined by a graph
5. Consider the following function defined by its graph:

y6
3

1 e
x
e 0 u -
−5 −4 −3 −2 −1 0 1 2 3 4 5
u
e e −1

u −2

−3

−4

Find the following limits:


a) lim f (x) b) lim f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−2− x→−2+ x→−2 x→−5 x→5

6. Consider the following function defined by its graph:


e e
u
y6
u
e e 3

2 u
e

1
x
0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
−1

−2

−3

−4

Find the following limits:


a) lim − f (x) b) lim + f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−2 x→−2 x→−2 x→−5 x→5


c 2009 La Citadelle 3 of 9 www.la-citadelle.com
CALCULUS Limits. Functions defined by a graph
7. Consider the following function defined by its graph:

y6
3 u
e

e 1
x
e
u e
u 0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
−1

−2

−3

−4

Find the following limits:


a) lim f (x) b) lim f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−2− x→−2+ x→−2 x→−4 x→5

8. Consider the following function defined by its graph:

y6
3

e
u e 1
x
e e
u 0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
−1 e
u

−2

−3

−4

Find the following limits:


a) lim − f (x) b) lim + f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−2 x→−2 x→−2 x→−3 x→5


c 2009 La Citadelle 4 of 9 www.la-citadelle.com
CALCULUS Limits. Functions defined by a graph
9. Consider the following function defined by its graph:

y6
3

1
x
u
e 0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
e −1 u
e e

−2 u

−3

−4

Find the following limits:


a) lim f (x) b) lim f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→2− x→2+ x→2 x→−4 x→4

10. Consider the following function defined by its graph:

y6
e 3

u 2

1
x
0 -
−5 −4 −3 −2 −1 0 1 2 3 4 5
u
e −1

e −2

−3 u
e

−4

Find the following limits:


a) lim − f (x) b) lim + f (x) c) lim f (x) d) lim f (x) e) lim f (x)
x→−2 x→−2 x→−2 x→−3 x→3


c 2009 La Citadelle 5 of 9 www.la-citadelle.com
www.la-citadelle.com 6 of 9 c 2009 La Citadelle

Answers: 1. a) 2 b) 2 c) 2 d) DN E e) DN E
2. a) 3 b) 3 c) 3 d) DN E e) DN E
3. a) − 2 b) − 2 c) − 2 d) DN E e) − 2
4. a) 2 b) 2 c) 2 d) 0 e) − 1
5. a) − 1 b) − 1 c) − 1 d) DN E e) 1
6. a) 3 b) 4 c) DN E d) DN E e) 2
7. a) 0 b) 0 c) 0 d) DN E e) 3
8. a) 0 b) 1 c) DN E d) DN E e) − 1
9. a) − 1 b) − 1 c) − 1 d) DN E e) − 1
10. a) 3 b) 3 c) 3 d) DN E e) − 3
Limits. Functions defined by a graph CALCULUS
CALCULUS Limits. Functions defined by a graph
Solutions:

1.
a) lim f (x) = 2
x→−1−
b) lim f (x) = 2
x→−1+
c) lim f (x) = lim f (x) . Therefore lim f (x) = 2
x→−1− x→−1+ x→−1
d) lim f (x) 6= lim f (x) . Therefore lim f (x) = DNE
x→−4− x→−4+ x→−4
e) lim− f (x) 6= lim+ f (x) . Therefore lim f (x) = DNE
x→4 x→4 x→4

2.
a) lim− f (x) = 3
x→1
b) lim+ f (x) = 3
x→1
c) lim f (x) = lim f (x) . Therefore lim f (x) = 3
x→1− x→1+ x→1
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−5 x→−5 x→−5
e) lim f (x) 6= lim f (x) . Therefore lim f (x) = DNE
x→5− x→5+ x→5

3.
a) lim f (x) = −2
x→−2−
b) lim f (x) = −2
x→−2+
c) lim f (x) = lim f (x) . Therefore lim f (x) = −2
x→−2− x→−2+ x→−2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−4 x→−4 x→−4
e) lim− f (x) = lim+ f (x) . Therefore lim f (x) = −2
x→3 x→3 x→3

4.
a) lim− f (x) = 2
x→2
b) lim+ f (x) = 2
x→2
c) lim f (x) = lim f (x) . Therefore lim f (x) = 2
x→2− x→2+ x→2
d) lim − f (x) = lim + f (x) . Therefore lim f (x) = 0
x→−4 x→−4 x→−4
e) lim f (x) = lim f (x) . Therefore lim f (x) = −1
x→5− x→5+ x→5

5.
a) lim f (x) = −1
x→−2−
b) lim f (x) = −1
x→−2+
c) lim f (x) = lim f (x) . Therefore lim f (x) = −1
x→−2− x→−2+ x→−2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−5 x→−5 x→−5
e) lim f (x) = lim f (x) . Therefore lim f (x) = 1
x→5− x→5+ x→5

6.
a) lim f (x) = 3
x→−2−
b) lim f (x) = 4
x→−2+
c) lim f (x) 6= lim f (x) . Therefore lim f (x) = DNE
x→−2− x→−2+ x→−2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−5 x→−5 x→−5
e) lim− f (x) = lim+ f (x) . Therefore lim f (x) = 2
x→5 x→5 x→5


c 2009 La Citadelle 7 of 9 www.la-citadelle.com
CALCULUS Limits. Functions defined by a graph
7.
a) lim f (x) = 0
x→−2−
b) lim f (x) = 0
x→−2+
c) lim f (x) = lim f (x) . Therefore lim f (x) = 0
x→−2− x→−2+ x→−2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−4 x→−4 x→−4
e) lim− f (x) = lim+ f (x) . Therefore lim f (x) = 3
x→5 x→5 x→5

8.
a) lim f (x) = 0
x→−2−
b) lim f (x) = 1
x→−2+
c) lim f (x) 6= lim f (x) . Therefore lim f (x) = DNE
x→−2− x→−2+ x→−2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−3 x→−3 x→−3
e) lim− f (x) = lim+ f (x) . Therefore lim f (x) = −1
x→5 x→5 x→5

9.
a) lim− f (x) = −1
x→2
b) lim f (x) = −1
x→2+
c) lim− f (x) = lim+ f (x) . Therefore lim f (x) = −1
x→2 x→2 x→2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−4 x→−4 x→−4
e) lim− f (x) = lim+ f (x) . Therefore lim f (x) = −1
x→4 x→4 x→4

10.
a) lim f (x) = 3
x→−2−
b) lim f (x) = 3
x→−2+
c) lim f (x) = lim f (x) . Therefore lim f (x) = 3
x→−2− x→−2+ x→−2
d) lim − f (x) 6= lim + f (x) . Therefore lim f (x) = DNE
x→−3 x→−3 x→−3
e) lim− f (x) = lim+ f (x) . Therefore lim f (x) = −3
x→3 x→3 x→3


c 2009 La Citadelle 8 of 9 www.la-citadelle.com